Na3V2(PO4)3 with specially designed carbon framework as high performance cathode for sodium-ion batteries. Issue 4 (March 2019) - Zheng, Li-Li; Xue, Yuan; Deng, Liang; Wu, Guo-Rui; Hao, Su-E.; Wang, Zhen-bo
Abstract: The structures of materials have great influence on their properties. For materials with low electron conductivity, fast electron transport pathway can be constructed through carbon structure design. Here we report a simple but effective method to improve the electrochemical performances of Na3 V2 (PO4 )3 . Polyvinyl Pyrrolidone (PVP) can improve the viscosity of the precursor solution, thus forming aggregate structured material. In Na3 V2 (PO4 )3, primary particles with a diameter of approximately 300 nm are aggregated through a special carbon network to form micro-sized secondary particles. This kind of structure will provide easy access for electron transportation, thereby improving electrochemical performance of the material. As a cathode material for sodium-ion batteries, Na3 V2 (PO4 )3 delivers excellent rate (86.6 mAh g −1 at 30 C) and cycling performance (capacity retention of 88.4% after 2000 cycles at 10 C). The material also exhibits a specific capacity of 100.2 mAh g −1 at 5 C under 55 °C. The above-mentioned performance is far better than the control sample without PVP. The special carbon network provides electron transport channels which improves the electrochemical performance of the material. This method may provide new ideas for the preparation of phosphate materials.